¿Cómo proteger jurídicamente al ser humano si se ignora su estructura existencial? - Fernández Sessarego, Carlos (Pontificia Universidad Católica del Perú, 2015)
The author makes a critical analysis of how over time it has tried to find the subject of study of Law and how it is distinguished from other beings that make up the universe. t hus the rational dimension of man has passed his ontological analysis as being in itself which makes it unique and spirit as the arrangement will be co-existential seeking protection for the same freedom he has. Finally, the author focuses on the own “freedom” of man and of which the other rights it has.

El autor hace un análisis crítico de cómo a lo largo del tiempo se ha tratado de encontrar al sujeto de estudio del Derecho y cómo este se distingue de los demás seres que conforman el universo. e s así como de la dimensión racional del ser humano se ha pasado a su análisis ontólogico como ser en sí mismo cuyo espíritu lo hace único y en tanto que ser coexistencial le procura el ordenamiento una protección por la misma libertad que posee. Finalmente el autor se centra en esa “Libertad” propia del ser humano que genera los demás derechos que posee.
How to legally protect humans if their existential structure is ignored?
Keywords: Freedom; Subject Law; Rational Being; Free Will; Co-Existential; Libertad; Sujeto de Derecho; Ser Racional; Libre Albedrio; Coexistencial; https://purl.org/pe-repo/ocde/ford#5.05.00